2009
DOI: 10.1029/2008ja013955
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Harang reversal and its dependence on plasma sheet conditions: Rice convection model simulations

Abstract: [1] The goal of this paper is to understand the formation of the Harang reversal and its association with the region 2 field-aligned current (FAC) system, which couples the plasma sheet transport to the ionosphere. We have run simulations with the Rice convection model (RCM) using the Tsyganenko 96 magnetic field model and realistic plasma sheet particle boundary conditions on the basis of Geotail observations. Our results show that the existence of an overlap in magnetic local time (MLT) of the region 2 upwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 26 publications
7
77
0
Order By: Relevance
“…The RCM is used to treat the transport of ions and electrons into the inner magnetosphere from the distant plasma sheet, modeling the proton and electron energy spectra with isotropic particle velocity space distributions for both species. The RCM's outer boundary is set at ≈20 R E , the proton and electron energy spectra at the boundary is established as a function of MLT and the interplanetary conditions, based on analysis of 11 years (1995–2005) of the Geotail LEP electron and ion fluxes from ≈0.04 to 40 keV data and the Geotail EPIC ion data (46 to 3000 keV) and assuming all ions are protons [ Wang et al , 2007, Gkioulidou et al , 2009]. The time‐dependent cross polar‐cap potential drop (ΔΦ PCP ) and the Z component of interplanetary magnetic field (IMF B z ) are used as inputs for both the outer particle boundary condition and for the T96 model.…”
Section: Ring Current Modelingmentioning
confidence: 99%
“…The RCM is used to treat the transport of ions and electrons into the inner magnetosphere from the distant plasma sheet, modeling the proton and electron energy spectra with isotropic particle velocity space distributions for both species. The RCM's outer boundary is set at ≈20 R E , the proton and electron energy spectra at the boundary is established as a function of MLT and the interplanetary conditions, based on analysis of 11 years (1995–2005) of the Geotail LEP electron and ion fluxes from ≈0.04 to 40 keV data and the Geotail EPIC ion data (46 to 3000 keV) and assuming all ions are protons [ Wang et al , 2007, Gkioulidou et al , 2009]. The time‐dependent cross polar‐cap potential drop (ΔΦ PCP ) and the Z component of interplanetary magnetic field (IMF B z ) are used as inputs for both the outer particle boundary condition and for the T96 model.…”
Section: Ring Current Modelingmentioning
confidence: 99%
“…Connections between substorm and region 2 electrodynamics have been found previously. These connections include simultaneous radar and optical observations, which have shown that auroral onsets tend to occur close to or equatorward of the Harang flow shear [ Baumjohann et al , 1981; Bristow et al , 2003; Zou et al , 2009a, 2009b], which results from region 2 magnetosphere‐ionosphere coupling and substantially distorts the duskside convection cell [ Erickson et al , 1991; Gkioulidou et al , 2009]. In addition, enhanced subauroral polarization streams (SAPS) have been found to be closely related to substorm onset and expansion phase development [ Lyons et al , 2009; Zou et al , 2009a, 2009b].…”
Section: Introductionmentioning
confidence: 99%
“…A convection structure of our particular interest is the Harang reversal [Harang, 1946], which in the ionosphere is characterized as the interface between the eastward and westward convection flows on its poleward and equatorward sides, respectively [Heppner, 1972;Maynard, 1974]. Modeling studies also suggest that ion thermal kinetics play an essential role in the formation of the Harang reversal in the magnetosphere [Erickson et al, 1991;Gkioulidou et al, 2009;Yang et al, 2014]. The associated latitudinal electric field converges at the reversal, suggesting that the reversal is collocated with an upward FAC; the distributions of convection and FACs are actually more complex because of the spatial gradient of ionospheric conductance (see section 4).…”
Section: Introductionmentioning
confidence: 99%